Regulation and Performance in the Distribution Sector - Pilat, Dirk (OECD Economics Department Working Papers, 1997)
This paper discusses the impact of government-imposed regulations on performance in the distribution sector. It first deals with the role of the distribution sector in OECD economies and gives an overview of competitive conditions in the sector. Next, it provides an overview of recent evidence concerning the impact of regulation. The paper finds that a range of regulations, including restrictions on large stores, opening hours and zoning, have slowed down structural change in the distribution sector. These regulations have sometimes reduced the efficiency of the distribution system, but have mainly limited the range of services provided to consumers ...